THE ROLE OF TEACHING WRITING IN THE PROCESS OF LANGUAGE LEARNING - Fayoza Ergasheva (International Scientific and Current Research Conferences, 2022)
This thesis examines the importance of teaching writing in language learning and the methods that are used for improving writing skills. Also, the reasons for teaching writing to learners are highlighted.